A Prospective Cohort Study in Nonhospitalized Household Contacts With Severe Acute Respiratory Syndrome Coronavirus 2 Infection: Symptom Profiles and Symptom Change Over Time. (28th July 2020) - Yousaf, Anna R; Duca, Lindsey M; Chu, Victoria; Reses, Hannah E; Fajans, Mark; Rabold, Elizabeth M; Laws, Rebecca L; Gharpure, Radhika; Matanock, Almea; Wadhwa, Ashutosh; Pomeroy, Mary; Njuguna, Henry; et al.
Abstract: Background: Improved understanding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spectrum of disease is essential for clinical and public health interventions. There are limited data on mild or asymptomatic infections, but recognition of these individuals is key as they contribute to viral transmission. We describe the symptom profiles from individuals with mild or asymptomatic SARS-CoV-2 infection. Methods: From 22 March to 22 April 2020 in Wisconsin and Utah, we enrolled and prospectively observed 198 household contacts exposed to SARS-CoV-2. We collected and tested nasopharyngeal specimens by real-time reverse-transcription polymerase chain reaction (rRT-PCR) 2 or more times during a 14-day period. Contacts completed daily symptom diaries. We characterized symptom profiles on the date of first positive rRT-PCR test and described progression of symptoms over time. Results: We identified 47 contacts, median age 24 (3–75) years, with detectable SARS-CoV-2 by rRT-PCR. The most commonly reported symptoms on the day of first positive rRT-PCR test were upper respiratory (n = 32 [68%]) and neurologic (n = 30 [64%]); fever was not commonly reported (n = 9 [19%]). Eight (17%) individuals were asymptomatic at the date of first positive rRT-PCR collection; 2 (4%) had preceding symptoms that resolved and 6 (13%) subsequently developed symptoms. Children less frequently reported lower respiratory symptoms (21%, 60%, and 69% for <18, 18–49, and ≥50 years of age, respectively; P = .03). Conclusions: Household contacts with laboratory-confirmed SARS-CoV-2 infection reported mild symptoms. When assessed at a single timepoint, several contacts appeared to have asymptomatic infection; however, over time all developed symptoms. These findings are important to inform infection control, contact tracing, and community mitigation strategies. Abstract : At the time of diagnosis, nonhospitalized household contacts with laboratory-confirmed severe acute respiratory syndrome coronavirus 2 infection most commonly had upper respiratory (68%) and neurologic (64%) symptoms; few (19%) reported fever, and 17% were asymptomatic.